2013
DOI: 10.1111/and.12100
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects ofFumaria parvifloraL. on lead-induced testicular toxicity in male rats

Abstract: In recent years, the clinical importance of herbal drugs has received considerable attention in reducing free radical-induced tissue injury. Oxidative stress has been proposed as a possible mechanism involved in lead toxicity that causes reproductive system failure in both human and animals. Fumaria parviflora L., a traditional herb, has been used to cure various ailments in Persian folk medicine. This study was carried out to investigate whether ethanolic extract of F. parviflora leaves could protect the male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 61 publications
8
38
0
Order By: Relevance
“…Rubio et al (2006) have stated that severe effects of lead on function of male genital system occur through changes in spermatogenesis and sperm function [37]. Various Overall, results of the lead effects on sperms in the current study are similar to those from other recent investigations [5,7,9,38]. Significant decreases in Sertoli and Leydig cells, height of germinal epithelium and diameter of seminiferous tubules in rats have been reported [5,9,38].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Rubio et al (2006) have stated that severe effects of lead on function of male genital system occur through changes in spermatogenesis and sperm function [37]. Various Overall, results of the lead effects on sperms in the current study are similar to those from other recent investigations [5,7,9,38]. Significant decreases in Sertoli and Leydig cells, height of germinal epithelium and diameter of seminiferous tubules in rats have been reported [5,9,38].…”
Section: Discussionsupporting
confidence: 88%
“…Kakkar et al (2005) have shown that disorders in structure and function of male genital system and quality of sperms are principal symptoms of exposure to lead [8]. Lead can be absorbed through respiration, digestion and skin and accumulated in body [9]. Heavy metals such as lead can show their toxic effects through the production of reactive oxygen species (ROS) or inhibition of antioxidant enzyme activity [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study lead acetate treatment resulted in an elevation in the level malondehyde and nitric oxide level and a decrease in the activity of catalase in testis tissue these findings are in accordance with those of (Dorostghoal, 2013;Sharma & Bhattacharya, 2015;Ansar et al, 2016) they attributed that to administration of lead, Lead can cross the blood-testis barrier, accumulate in the testis, and damage germinal cells at various levels of differentiationshifted the oxidant/antioxidant profile towards oxidant side as manifested by the marked exhaustion of the enzymatic antioxidants together with the accumulation of lipid peroxidation product in the testicular tissue homogenate. This was in corroboration with earlier reports (Ansar et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…83 It has been reported phenolic compounds present in Fumaria parviflora leaves demonstrated significant protection against lead induced testicular oxidative stress in rats. 84 Cinnamon polyphenols witnessed significant protection against lead acetate induced reproductive toxicities in male rats. 85 Rich phenolic compounds present in Tribulus terrestris root extract and vitamin C have preventive role against lead acetate induced testicular toxicity in mice.…”
Section: Effect Of Polyphenol Against Lead Induced Reproductive Toxicitymentioning
confidence: 99%